Neurosurgery education of medical students in Nicolaus Copernicus University during the COVID-19 pandemic - Zygmunt Siedlecki; Karol Nowak; Maciej Śniegocki (Kazimierz Wielki University, 2020)
We present a short article on the actual state of education and didactics in the Department of Neurosurgery during the COVID-19 pandemic. The pandemic disrupted the education of students in the 2019/2020 and 2020/2020 academic years. From March 2020, there are no traditional classes with students and they have been deprived the possibility of patients examining and participating in surgical procedures. Only on-line classes are conducted by the use of Microsoft Teams and by e-mail contact. We emphasize that this is unprecedented situation in history of clinical medicine education. We also affirm difficulty of surgical medical specializations training by e-learning. Due to the practical nature of neurosurgery, we provide numerous neuroimaging and videos of surgical procedures using Microsoft Teams. The effects of on-line education of surgical sciences, including neurosurgery, can be assessed after a longer period of time. Currently, in the new reality that surprised unexpectedly medical academics in 2020, we are unable to interpret it.